2006
DOI: 10.1507/endocrj.k06-018
|View full text |Cite
|
Sign up to set email alerts
|

Subclinical Hypothyroidism Is Associated with Early Insulin Resistance in Kuwaiti Women

Abstract: Abstract. Subclinical hypothyroidism (SH), defined as an asymptomatic state characterized by normal serum concentrations of free thyroxine and elevated serum concentrations of TSH. The aim of this study is to investigate the complex interplay between insulin resistance and low grade chronic inflammation in Kuwaiti women with subclinical hypothyroidism. Thirty four women with subclinical hypothyroidism (SH) and 20 healthy women as controls matched to the patient group for sex, age and body mass index (BMI), wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
46
0
3

Year Published

2009
2009
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(52 citation statements)
references
References 22 publications
3
46
0
3
Order By: Relevance
“…Yet, the results of other studies indicate a normal insulin sensitivity in that group of patients [34,35].…”
Section: Hypothyroidismmentioning
confidence: 74%
“…Yet, the results of other studies indicate a normal insulin sensitivity in that group of patients [34,35].…”
Section: Hypothyroidismmentioning
confidence: 74%
“…They found that the insulin levels were significantly higher in the Subclinical hypothyroidism group comparable to the normal control. 15 Another study by Christy et al selected 30 hypothyroid, non-diabetic patients with normocytic normochromic anaemia and compared these patients with 30 euthyroid non-diabetic patients also with normocytic normochromic anaemia. HbA1c in the hypothyroid patients was 6.32±0.75% versus 5.87±0.46% in the euthyroid group, the difference being statistically significant.…”
Section: Discussionmentioning
confidence: 99%
“…In this condition, data regarding insulin effects on glucose metabolism are contradictory: insulin sensitivity in the fasting state (assessed with homeostasis model assessment (HOMA) index) has been found to be either normal (5,6) or decreased (7). However, in patients with SHO, fasting hyperinsulinemia has been reported (7,8).…”
Section: Introductionmentioning
confidence: 99%